2018
DOI: 10.1093/sleep/zsy260
|View full text |Cite|
|
Sign up to set email alerts
|

On-the-road driving performance the morning after bedtime administration of lemborexant in healthy adult and elderly volunteers

Abstract: Study Objectives To assess potential effects of lemborexant on next-morning driving performance in adult and elderly healthy volunteers. Methods Randomized, double-blind, double-dummy, placebo and active-controlled, four period incomplete crossover study in 48 healthy volunteers (22 females), 23–78 years old. Participants were treated at bedtime for eight consecutive nights with two of three dose levels of lemborexant (2.5, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 213 publications
(50 citation statements)
references
References 29 publications
(34 reference statements)
2
48
0
Order By: Relevance
“…The lack of an effect of plasma lemborexant accumulation on next‐morning residual sleepiness may be attributed to the orexin receptor occupancy threshold and the competition with endogenous orexin for receptor sites. Consistent with these PK/PD findings, single and repeated doses of lemborexant (2.5, 5, or 10 mg) had no clinically meaningful residual effect on next‐morning on‐road driving performance (9 hours after bedtime dosing) in a phase 1, randomized controlled study involving healthy adults and elderly subjects 23 …”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The lack of an effect of plasma lemborexant accumulation on next‐morning residual sleepiness may be attributed to the orexin receptor occupancy threshold and the competition with endogenous orexin for receptor sites. Consistent with these PK/PD findings, single and repeated doses of lemborexant (2.5, 5, or 10 mg) had no clinically meaningful residual effect on next‐morning on‐road driving performance (9 hours after bedtime dosing) in a phase 1, randomized controlled study involving healthy adults and elderly subjects 23 …”
Section: Discussionsupporting
confidence: 57%
“…Consistent with these PK/PD findings, single and repeated doses of lemborexant (2.5, 5, or 10 mg) had no clinically meaningful residual effect on next-morning on-road driving performance (9 hours after bedtime dosing) in a phase 1, randomized controlled study involving healthy adults and elderly subjects. 23 In all 3 studies lemborexant was well tolerated at doses representing large multiples (up to 200 mg as a single dose and up to 75 mg as multiple doses for 14 days) of the highest dose (10 mg) currently approved for the treatment of insomnia and had a favorable safety profile, consistent with the mechanism of action. The safety and tolerability profiles were similar between adults and elderly subjects and between Japanese and white subjects, indicating that no age-or race-based dose adjustments are likely to be needed.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that bedtime dosing of LEM is not associated with clinically important morning residual effects, such as reduced postural stability upon awakening (in older participants with insomnia disorder and in healthy older adults) or impaired driving performance in the morning in healthy adult and elderly volunteers [ 28 , 29 ]. Other common TEAEs (those occurring in >2% of participants in any active treatment group) such as headache, influenza, and upper respiratory tract infection occurred at similar rates in the LEM and placebo groups.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, a similar incidence of treatment-emergent adverse events (TEAEs) was observed in the placebo and LEM treatment groups, and most TEAEs were mild or moderate in severity. In addition, LEM did not impair morning driving ability in healthy adult volunteers following bedtime dosing [ 28 ]. LEM also did not impact the ability of healthy older volunteers to awaken to an acoustic stimulus in the middle of the night, nor did LEM affect postural stability (an indicator of falls risk) at morning waketime.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical in vivo assessments in rodents have shown that lemborexant exerts a sleep-promoting effect via the orexin signaling pathway (Beuckmann et al, 2019). In clinical studies, including two pivotal phase 3 studies, lemborexant improved sleep onset and sleep maintenance with minimal next-morning residual sleepiness and no significant impairment of next-morning driving performance in insomnia patients (Murphy et al, 2017;Rosenberg et al, 2019;Vermeeren et al, 2019). Based on these and other data, lemborexant was approved for the treatment of insomnia by the U.S.…”
Section: Introductionmentioning
confidence: 99%